2023
DOI: 10.1186/s13550-023-00977-4
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of [18F]FDG PET/CT radiomics combined with clinical features for EGFR mutation status in different clinical staging of lung adenocarcinoma

Abstract: Background This study aims to construct radiomics models based on [18F]FDG PET/CT using multiple machine learning methods to predict the EGFR mutation status of lung adenocarcinoma and evaluate whether incorporating clinical parameters can improve the performance of radiomics models. Methods A total of 515 patients were retrospectively collected and divided into a training set (n = 404) and an independent testing set (n = 111) according to their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The expression of BATF could be a potential selective criterion of anti-cancer therapeutics, which could only be detected after surgery and could not be monitored repeatedly and dynamically. As a whole-body molecular imaging modality, 18 F-FDG PET/CT plays an important role in tumor diagnosis, staging and treatment outcome in CRC [ 35 ]. The PET-related parameters include the SUV max , MTV, and TLG, which were reported to be positively correlated with the malignancy of multiple tumors, including CRC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BATF could be a potential selective criterion of anti-cancer therapeutics, which could only be detected after surgery and could not be monitored repeatedly and dynamically. As a whole-body molecular imaging modality, 18 F-FDG PET/CT plays an important role in tumor diagnosis, staging and treatment outcome in CRC [ 35 ]. The PET-related parameters include the SUV max , MTV, and TLG, which were reported to be positively correlated with the malignancy of multiple tumors, including CRC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have examined the usefulness of 18 F-FDG PET/CT radiomics-based ML analysis for predicting gene mutation. Previous studies commonly showed that 18 F-FDG PET/CT radiomics-based ML analysis had a promising performance for predicting gene mutation [ 33 39 ] (Table 1 ). Gao et al [ 33 ] constructed radiomics-based models based on 18 F-FDG PET/CT features using ML to predict EGFR mutation status in patients with lung ADC.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…Previous studies commonly showed that 18 F-FDG PET/CT radiomics-based ML analysis had a promising performance for predicting gene mutation [ 33 39 ] (Table 1 ). Gao et al [ 33 ] constructed radiomics-based models based on 18 F-FDG PET/CT features using ML to predict EGFR mutation status in patients with lung ADC. Results showed that the ML model with the random forest (RF) algorithm using combined clinical data, CT-radiomics and PET-radiomics had the highest performance, with an AUC of 0.730.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…Also, our previous study ( 12 ) has shown that machine learning model based on PET/CT handcrafted radiomics features (HRFs) achieved a good prediction performance in the identification of EGFR mutation status and subtypes in lung adenocarcinoma. Recently, the value of PET/CT-based HRFs in predicting EGFR mutation status, EGFR subtypes and prognosis had been well demonstrated ( 12 18 ), which involved different feature selection methods and machine learning algorithms. These different radiomics pipelines may lead to various predictive performance ( 19 ).…”
Section: Introductionmentioning
confidence: 99%